A Framework for Business-to-Business E-Commerce Evaluation Challenges and Critical Success Factors - Lin, Chad; Huang, Y. (World Scientific Publishing, 2009)
Business-to-business e-commerce (B2BEC) which deals with Internet-supported commercial activities between two or more different companies is becoming increasingly imperative for companies aiming at improving their competitiveness and this has led to much of research and new IT investments. Its growth outpaced all of other forms of electronic commerce. However, the potential for realizing significant benefits for implementation of B2BEC does not appear to have been enough to provide impetus for extensive adoption by organizations. Although B2BEC provides the organizations a wealth of new opportunities and ways of doing business, it also presents them with a series of challenges. Therefore, the case study approach was utilized to investigate the process of B2BEC investment evaluation in nine Australian organizations within the hospitality sector. The key objectives of this exploratory research are: (1) to establish current practices and norms in managing B2BEC evaluation in Australian organizations; and (2) to development a framework of challenges and critical success factors in B2BEC evaluation. A key contribution of the book chapter is to identify and examine challenges and critical success factors faced by Australian organizations undertaking B2BEC evaluation. Moreover, a framework was proposed for Australian organizations to measure their B2BEC investments.